Strategi pembelajaran berdasarkan sudut kegiatan untuk peningkatan mutu pendidikan di TK Aisyiyah Bustanul Athfal Kricak Kidul Tegalrejo Yogyakarta 2013/2014 - Sri Endah Winarni; Mundilarno Mundilarno (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aims to describe the learning strategy based on the student's activity which was held at private Pupils of Kricak Kidul Yogyakarta which includes the teaching and learning process, implementation, and learning assessment as an effort to improve the quality of the education. This was a qualitative naturalistic research. The subject of this research was the principal, teachers, parents and Pupils of Aisyiyah Bustanul Atfal Kricak Kidul Yogyakarta’s students. The object of the research was the improvement of education quality based on student activity. Data were collected by interview, observation, documentation, and analyzed descriptively. The result revealed that the teachers understand about their main jobs take as role as executor of learning based on student activity. They understand the steps to implement the learning process based on students activity such as the teacher have planning, implementing, execute assessment, analysis and then follow up of the problem to improve the learning process. Parents fully understand their role so that their student's success in schooling. The student fully understands that learning that match with their activity, and the school principal as a quality controller understand her duty to improve the quality of learning in her school. Although the facilities in the Kindergarten Aisyiyah Bustanul Atfal Kricak KidulYogyakarta good enough, it is very important to improve the teaching media in order to improve education quality of the Kindergarten of Aisyiyah Bustanul Atfal Kricak Kidul Yogyakarta.